Fresno County Bar Association Old Timers' Luncheon at Plaza Ballroom - Watkins, Howard::::::::: (1987)
Emcee Charles Barrett, Jr., Howard Thomas, Lawrence Kennedy, Robert Wash, Max Hayden, Miles Hansen, Archives Committee Chair Marian Mosley, Stephen Blumberg and Fresno County Bar Association President Howard Watkins